Perbandingan Fiqih Jual Beli (Bai’), Perdagangan (Tijarah), Pilihan (Khiyar), dan Pengambilalihan Hak Pengelolaan Harta (Syuf’ah): A Comparative Jurisprudence of Sale and Purchase (Bai’), Commerce (Tijarah), Contractual Options (Khiyar), and the Right of Pre-emption (Syuf’ah) - Muhamad Afif Sholahudin; Dedah Jubaedah; Iwan Setiawan (Litera Academica Publishing, 2026)
Studies in fiqh muamalah often place tijārah (commerce), ba’i (sale), khiyār (contractual options), and syuf‘ah (pre-emption) into separate analytical spheres, leading to a fragmented understanding of the Islamic transactional system. This research aims to develop a holistic theoretical construction by comparatively examining the definitions, legal foundations, scopes, and functions of these four concepts. The methodology employed is normative legal research with a library-based approach, involving a critical analysis of primary sources—the Qur'an, Hadith, and classical fiqh texts—as well as secondary sources such as scientific journals and contemporary regulations. The findings indicate that tijārah serves as a philosophical framework emphasizing economic ethics and spirituality, while ba’i acts as a formal-legal instrument regulating the validity of exchange. Furthermore, khiyār functions as an internal protection mechanism for the contracting parties, and syuf‘ah serves as an external protection mechanism for joint ownership. The integration of these four concepts establishes an Islamic transactional system that is just, adaptive, and contextual, remaining relevant to modern practices such as e-commerce, private equity ownership, and Islamic financial institutional financing. This study underscores the necessity of an integrative approach in fiqh muamalah to strengthen the relevance of Islamic law within contemporary economic dynamics.